Congenital Long QT Syndrome: An Update and Present Perspective in Saudi Arabia - Bhuiyan, M. Z. A.; Al-Shahrani, Safar; Al-Aama, Jumana; Wilde, Arthur; Momenah, Tarek S. (Frontiers in Pediatrics, 2013)
Primary cardiac arrhythmias are often caused by defects, predominantly in the genes responsible for generation of cardiac electrical potential i.e. cardiac rhythm generation. Due to the variability in underlying genetic defects, type and location of the mutations and putative modifiers, clinical phenotypes could be moderate to severe, even absent in many individuals. Clinical presentation and severity could be quite variable, syncope or sudden cardiac death (SCD) could also be the first and the only manifestation in a patient who had previously no symptoms at all. Despite usual familial occurrence of such cardiac arrhythmias, disease causal genetic defects could also be de novo in significant number of patients. Long QT syndrome (LQTS) is the most eloquently investigated primary cardiac rhythm disorder. A genetic defect can be identified in ~70% of definitive LQTS patients, followed by Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) and Brugada syndrome (BrS), where a genetic defect is found in